Chondroitin sulfate efficacy versus celecoxib on knee osteoarthritis structural changes using magnetic resonance imaging: a 2-year multicentre exploratory study. Issue 1 (December 2016) - Pelletier, Jean-Pierre; Raynauld, Jean-Pierre; Beaulieu, André; Bessette, Louis; Morin, Frédéric; de Brum-Fernandes, Artur; Delorme, Philippe; Dorais, Marc; Paiement, Patrice; Abram, François; Martel-Pelletier, Johanne
Abstract Background In osteoarthritis (OA) treatment, although chondroitin sulfate (CS) was found in a number of studies using radiography to have a structure-modifying effect, to date CS use is still under debate. A clinical study using quantitative magnetic resonance imaging (qMRI) is therefore of the utmost importance. Here we report data from a 24-month, randomised, double-blind, double-dummy, controlled, comparative exploratory study of knee OA. The primary endpoint was to determine the effect of CS 1200 mg/day versus celecoxib 200 mg/day on cartilage volume loss (CVL) in the lateral compartment over time as measured by qMRI. Secondary endpoints included assessment of the OA structural changes and signs and symptoms of OA. Methods qMRI was performed at baseline and at 12 and 24 months. CVL, bone marrow lesion size, and synovial thickness were evaluated using qMRI. The primary statistical analysis was carried out on the modified intention-to-treat (mITT) population (n  = 138) using chi-squared, Fisher's exact, Wilcoxon Mann–Whitney, and Student'st tests and analysis of covariance. Analyses were also conducted on the according-to-protocol (ATP;n  = 120) population. Results In the adjusted mITT analysis, compared with celecoxib treatment, patients treated with CS had a significant reduced CVL at 24 months in the medial compartment (celecoxib –8.1 % ± 4.2, CS –6.3 % ± 3.2;p  = 0.018) and medial condyle (–7.7 % ± 4.7, –5.5 % ± 3.9;p  = 0.008); no significant effect was seen in the lateral compartment. In the ATP population, CS reduced CVL in the medial compartment at 12 months (celecoxib –5.6 % ± 3.0, CS –4.5 % ± 2.6;p  = 0.049) and 24 months (celecoxib –8.4 % ± 4.2, CS –6.6 % ± 3.3;p  = 0.021), and in the medial condyle at 24 months (celocoxib –8.1 % ± 4.7, CS –5.7 % ± 4.0;p  = 0.010). A trend towards a statistically reduced synovial thickness (celecoxib +17.96 ± 33.73 mm, CS –0.66 ± 22.72 mm;p  = 0.076) in the medial suprapatellar bursa was observed in CS patients. Both groups experienced a marked reduction in the incidence of patients with joint swelling/effusion and in symptoms over time. Data showed similar good safety profiles including cardiovascular adverse events for both drugs. Conclusion This study demonstrated, for the first time in a 2-year randomised controlled trial using qMRI, the superiority of CS over celecoxib at reducing CVL in knee OA patients. Trial registration ClinicalTrials.govNCT01354145 . Registered 13 May 2011.